Synthesis, Characterization, and Anti-Breast Cancer Properties of Cu(II) Complexes with Schiff Base and Azo Dye Ligands - Abbas, Haneen Fadhil; Aldoghachi, Faris Jassim; Salih, Basil Abdulmahdi; Taufiq-Yap, Yun Hin (Universitas Gadjah Mada, 2025)
This article focuses on the synthesis of three Schiff base ligands derived from 2-hydroxybenzaldehyde (B: BBr, BOCH3, BNO2) and three azo dye ligands derived from naphthol (A: ABr, AOCH3, ANO2), followed by the preparation of copper(II) complexes with these six ligands in a 1:2 (metal:ligand) ratio. The ligands and complexes were characterized by using 1H-NMR, 13C-NMR, FTIR, UV-vis, and ESI-MS. Thermogravimetric and differential thermal analyses of the copper complexes indicated the absence of water molecules in the crystalline coordination, demonstrating high thermal stability. The findings confirmed the formation of square-planar copper complexes. The biological activity of the complexes was evaluated on breast cancer and healthy cells using the MTT assay at different concentrations. The IC50 analysis showed that CuABr, CuBBr, and CuAOCH3 had a significantly more substantial cytotoxic effect on cancer cells than on healthy cells. CuBOCH3 and CuBNO2 also exhibited notable selectivity toward cancer cells, whereas CuANO2 was more toxic to normal cells. These findings highlight the potential of CuABr, CuBBr, and CuAOCH3 as promising candidates for further development in targeted breast cancer therapy.